2020
DOI: 10.1007/s12598-020-01463-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent progresses on alloy-based anodes for potassium-ion batteries

Abstract: Potassium-ion batteries (KIBs) are one of the most promising large-scale electric energy storage systems due to the high abundance and low redox potential of K. As the key component, anode determines their energy density and safety. Alloy-based anodes, such as P, Sn, Sb, and Bi, have attracted extensive attention due to their abundant resources, suitable working potentials, and large theoretical capacities. However, the dramatic volume variation upon (de)potassiation results in pulverization of particles and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 103 publications
(113 reference statements)
0
27
0
Order By: Relevance
“…40,41 The major shortcoming of alloying-type materials is the structural instability caused by the huge volume expansion during K insertion. 42 This leads to the pulverisation of the materials and poor cycling stability. In the case of electrochemically storing K + in Sn, the formation of the intermediate phase K 4 Sn 9 and nal phase KSn led to a volume change of 113% and 197%, respectively.…”
Section: Challenges Of Electrode Materials In Kibsmentioning
confidence: 99%
“…40,41 The major shortcoming of alloying-type materials is the structural instability caused by the huge volume expansion during K insertion. 42 This leads to the pulverisation of the materials and poor cycling stability. In the case of electrochemically storing K + in Sn, the formation of the intermediate phase K 4 Sn 9 and nal phase KSn led to a volume change of 113% and 197%, respectively.…”
Section: Challenges Of Electrode Materials In Kibsmentioning
confidence: 99%
“…[4,5] Studies have shown that the antimonybase alloy is an ideal option for K þ /Na þ storage due to high theoretical gravimetric capacity (660 mAh g À1 ) based on the multielectron reaction and relative safe voltage, which can effectively inhibit the continuous solidÀelectrolyte interface film. [6][7][8][9] Unfortunately, the severe volume change of antimony during the alloying/dealloying process will cause electrode pulverization and lead to rapid capacity fading, which hinders the application of antimony-based materials. To ameliorate the electrochemical performance of antimony anode, many effective methods have been actively explored.…”
Section: Introductionmentioning
confidence: 99%
“…Battery energy storage systems (BESSs) are an indispensable technology due to the global growth in electric energy consumption. Although various types of BESSs are available [ 1 , 2 , 3 , 4 ], most BESSs consist of lithium ion batteries (LIBs) because of their many advantages, such as high energy density and efficiency. However, in the BESS field, size enlargement of LIBs has proven difficult, and they also exhibit a safety issue.…”
Section: Introductionmentioning
confidence: 99%